Developing a Learning Model Based on Hybrid Learning and PjBL - Sabir Ramadhan, Muhammad; ., Rumondang (KnE Social Sciences, 2023)
Currently, student interest in teaching and learning in schools is declining, coupled with high youth unemployment, the same is also happening in universities. The existing learning model is only teacher-oriented, tends to be passive in order to reduce the nature of learning, students must continually build new ideas based on their learning experiences in order to be able to think creatively and solve problems in the material presented by the teacher. The model of electronic learning (e-learning) in higher education institutions that takes advantage of the advantages of information and communication technologies (ICT), offers a concept of learning where there is a transformation of learning from conventional form to digital form, both in content and in system. has shortcomings, namely not having interaction in the learning process; Project-based learning (PjBL) is one of the innovative learning implemented, but it has not had a sufficient impact on increasing the activity, creativity and productivity of students, especially in the design of a project. This study aims to determine the needs desired by lecturers and students in implementing learning in the multimedia and animation technology course. Results of research that based on the needs analysis performed, students expect the presence of a new learning model that can maximize learning. Based on the needs analysis carried out, the teacher expects a new learning model capable of maximizing learning. Lecturers and students expect a learning model capable of collaborating in the use of information technology and skills required in the 21st century. Keywords: Hybrid learning; PjBL; learning model; multimedia; animation